The Gallic Acid–Phospholipid Complex Improved the Antioxidant Potential of Gallic Acid by Enhancing Its Bioavailability - Bhattacharyya, Sauvik (Springer US, 2013)
Gallic acid (GA) is well known for its antioxidant and hepatoprotective activity, though its effectiveness is restricted due to rapid metabolism and elimination. To overcome these problems, gallic acid–phospholipid complex was prepared and the effect of phospholipid complexation was investigated on carbon tetrachloride (CCl(4))-induced oxidative damage in rat liver. The complex significantly reduced the hepatic marker enzymes in rat serum and restored the antioxidant enzyme levels with respect to CCl(4)-induced group (P < 0.05 and P < 0.01). Also, the complex improved the pharmacokinetics of GA by increasing the relative bioavailability and elimination half-life. The study therefore suggests that phospholipid complexation has enhanced the therapeutic efficacy of GA which may be due to its improved absorption and increased bioavailability in rat serum. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1208/s12249-013-9991-8) contains supplementary material, which is available to authorized users.